2012
DOI: 10.1111/dgd.12025
|View full text |Cite
|
Sign up to set email alerts
|

Magnetoreception and baroreception in birds

Abstract: The world as we know it is defined by our senses, although as humans we are equipped to receive and interpret only a fraction of the potential sensory information available. Birds have evolved with different sensory priorities to our own; they can use the Earth's magnetic field as a navigational aid, and are sensitive to slight changes in barometric pressure. These abilities help explain the impressive ability of many bird species to orientate, navigate, and maintain steady altitude during flight over long dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 102 publications
(157 reference statements)
0
14
0
1
Order By: Relevance
“…In quail, its detachment is simply the result of the loss of its proximal region with no observable translation. The PTO is present in a wide range of avian species with the exception of all investigated paleognathous birds (Starck, ) and a few neognathous species (Neeser & von Bartheld, ; see review, Giannessi et al, ; O'Neill, ; von Bartheld & Giannessi, ). The shared developmental origin and presence in a wide range of birds justifies the PTO to be an important landmark to help define the developmental pattern of the paratympanic sinuses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In quail, its detachment is simply the result of the loss of its proximal region with no observable translation. The PTO is present in a wide range of avian species with the exception of all investigated paleognathous birds (Starck, ) and a few neognathous species (Neeser & von Bartheld, ; see review, Giannessi et al, ; O'Neill, ; von Bartheld & Giannessi, ). The shared developmental origin and presence in a wide range of birds justifies the PTO to be an important landmark to help define the developmental pattern of the paratympanic sinuses.…”
Section: Discussionmentioning
confidence: 99%
“…The function of this sensory organ in birds remains unresolved and no direct experimental study has been made yet (see review, Giannessi et al, ; O'Neill, ; von Bartheld & Giannessi, ). However, based on the connection of the PTO and tympanic membrane to the PTOL, and a preliminary experimental study (von Bartheld, ), it is suggested that the PTO with hair cells functions as a barometer and/or altimeter (von Bartheld & Giannessi, ).…”
Section: Discussionmentioning
confidence: 99%
“…Another magnetically sensitive structure is associated with the inner ear in the lagena (Wu and Dickman 2011), which may also be integrated with the baroreceptive paratympanic organ D r a f t (O'Neill 2013). Lesioning the lagena suggested processing roles for the lateral hyperpallium, hippocampus, dorsal thalamus, and caudal vestibular nuclei, with a potential role of the vestibular brainstem as a magnetoreception integration site (Wu and Dickman 2012).…”
Section: Baro-and Magneto-receptionmentioning
confidence: 99%
“…Certain anaerobic bacteria, flighted birds, among many other life forms, possess magnetoreception-see, e.g., Refs. [27][28][29][30]. The central mechanisms underpinning biological magnetoreception, however, are still under debate.…”
mentioning
confidence: 99%
“…The central mechanisms underpinning biological magnetoreception, however, are still under debate. For instance, in the case of avian magnetoreception [30], no magnetoelectric organ or material constituent has been found. While small iron-oxide "magnetite" crystals with a relative magnetic permeability μ r at the order of 10 2 -10 5 are found in magnetoreceptive cells, the mechanism that will allow magnetic signals to be interpreted electrically has not been elucidated.…”
mentioning
confidence: 99%